Desain DESAIN USER INTERFACE PADA TOKO ONLINE HELM INDONESIA BERBASIS WEB - Teguh Khristianto; Isworo Nugroho; Dwi Agus Diartono; R.Soelistijadi R.Soelistijadi (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The growth rate of internet users in recent years has increased very rapidly and is growing rapidly. This triggers the creation of a new business model in the form of a marketplace that is used to buy and sell goods. This study aims to load an online store that is simple and lightweight but can meet the needs of sellers who use this website. Application development uses methods while the prototype in modeling the application uses use case diagrams, class diagrams, activity diagrams, and sequence diagrams. The research is expected to produce a web-based marketplace application that facilitates the transaction process of consignment providers and consumers at the Indonesian Helmet Shop. Furthermore, the design of this messaging service application prototype still needs to be developed in terms of user interface and user experience so that consumers can be more comfortable in transacting.